2019
DOI: 10.5435/jaaos-d-18-00105
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Skin Antiseptics Used in Orthopaedic Surgery Procedures

Abstract: Surgical site infections (SSIs) in orthopaedics are a common complication, with more than half a million SSIs occurring in the United States each year. SSIs can carry a notable burden for patients and physicians alike. Skin antiseptic solution plays an important role in preventing SSI. Many studies have looked at different skin antiseptic solution in preventing SSIs. Different surgical preps can decrease bacterial loads at surgical sites in varying degrees. Yet, the amount of bacterial load does not always cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 42 publications
0
24
0
1
Order By: Relevance
“…The purpose of pre-incisional skin preparation is to reduce radically (within several minutes after application) the number of bacteria at the site of the operating field prior to incision and control for recolonization during surgery [105]. A wide spectrum of paint solutions, including both alcohol-and non-alcohol-based agents, have been certified for this purpose [106], but evidence for a particular product is limited. A recent systematic review and meta-analysis found superior benefit for chlorhexidine compared to povidone-iodine in clean surgery in terms of prevention of postoperative SSIs (risk ratio 0.81; 95% CI, 0.67-0.98) [107].…”
Section: Preparation Of Operative Fieldmentioning
confidence: 99%
“…The purpose of pre-incisional skin preparation is to reduce radically (within several minutes after application) the number of bacteria at the site of the operating field prior to incision and control for recolonization during surgery [105]. A wide spectrum of paint solutions, including both alcohol-and non-alcohol-based agents, have been certified for this purpose [106], but evidence for a particular product is limited. A recent systematic review and meta-analysis found superior benefit for chlorhexidine compared to povidone-iodine in clean surgery in terms of prevention of postoperative SSIs (risk ratio 0.81; 95% CI, 0.67-0.98) [107].…”
Section: Preparation Of Operative Fieldmentioning
confidence: 99%
“…CHL, which is a common, inexpensive, safe, and efficacious antiseptic agent exhibited promising performance. CHL is functions by binding to cell membranes and thereby impairing bacterial adhesion and driving the leakage of bacterial cellular contents [8]. Most bacterial and Candida species have been shown to be killed by 1-2% CHL solutions [9], while CHL concentrations of 1% or lower have been shown to be safe when used for ophthalmic purposes [10].…”
Section: Discussionmentioning
confidence: 99%
“…The number of patients with purulent and long-term nonhealing wounds and the effectiveness of their treatment with the use of existing medical standards and medicines remain the same [1,2]. Therefore, the issue of developing new medicines and innovative methods of treating purulent diseases remains very relevant [3].…”
Section: краткие сообщенияmentioning
confidence: 99%
“…Гуревич 2 , А.Л. Ураков 3,* 1 Фармацевтический институт Крави, Индия, Хайдарабад 2 Московский государственный медико-стоматологический университет имени А.И. Евдокимова, Россия, Москва 3 Ижевская государственная медицинская академия, Россия, Удмуртская Республика, Ижевск * Контакты: Ураков Александр Ливиевич, e-mail: urakoval@live.ru…”
unclassified